2000
DOI: 10.1002/(sici)1097-4695(20000215)42:3<347::aid-neu6>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Sustained upregulation in embryonic spinal neurons of a Kv3.1 potassium channel gene encoding a delayed rectifier current

Abstract: Differentiation of electrical excitability entails changes in the currents that generate action potentials in spinal neurons of Xenopus embryos, resulting in reduced calcium entry during impulses generated at later stages of development. A dramatic increase in delayed rectifier current (I(Kv)) during the first day of development plays the major role in this process. Identification of potassium channel genes responsible for the increase in I(Kv) is critical to understanding the molecular mechanisms involved. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…Many K + channel genes are regulated developmentally. For example, Kv3.1 is upregulated throughout the development period, which contributes to the maturation of I Kv and shortening of the action potential 30 . Our results showed that the three predominant tandem‐pore K + channel genes are expressed at levels in embryonic rat ventricle that are much lower than their expression in adult heart, indicating that TWIK‐2 , TASK‐1 and TREK‐1 must also experience the upregulation process.…”
Section: Discussionmentioning
confidence: 76%
“…Many K + channel genes are regulated developmentally. For example, Kv3.1 is upregulated throughout the development period, which contributes to the maturation of I Kv and shortening of the action potential 30 . Our results showed that the three predominant tandem‐pore K + channel genes are expressed at levels in embryonic rat ventricle that are much lower than their expression in adult heart, indicating that TWIK‐2 , TASK‐1 and TREK‐1 must also experience the upregulation process.…”
Section: Discussionmentioning
confidence: 76%
“…During embryonic and postnatal development, Kv3 channels transcripts are upregulated in various CNS regions in rats (Perney et al 1992; Gurantz et al 2000), as well as in Xenopus (Gurantz et al 2000). Expression of Kv1 channels also increases during development in culture (Gurantz et al 1996; Grosse et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, presynaptic K + currents ( I pK ) might also undergo developmental change and contribute to the action potential shortening. Developmental changes in K + currents have been reported in postsynaptic neurons (Harris et al 1988; O'Dowd et al 1988; Gurantz et al 1996; Gurantz et al 2000; Riazanski et al 2001; Hattori et al 2003). However, little is known about developmental changes in K + currents at the nerve terminal.…”
mentioning
confidence: 99%
“…Its delayed rectifier properties can sustain high response rates (Kaczmarek and Perney, 1994; Perney and Kaczmarek, 1997). Hence the factors that regulate its expression during development may be related to the differentiation of electrical excitability (Shibata et al, 1999; Gurantz et al, 2000) and presumably synaptic activity. Response rate plays an important role in signal coding by certain types of neurons in the auditory system (see, e.g., Morest, 1993).…”
Section: Introductionmentioning
confidence: 99%